Bioprospecting of Halophilic Bacteria Staphylococcus Haemolyticus Strain Stp-Griv-024 as Biosurfactant Producer and its Potential Application for Microbial Enhanced Oil Recovery - Izzul Islam; Cut Nanda Sari; Ali Budhi Kusuma; Ika Kurniasari; Lisnawati Lisnawati; Rini Surya Ningsih; Elisa Rosani (Scientific Contributions Oil and Gas, 2024)
The use of halophilic bacteria to produce effective and stable biosurfactants in the Microbial Enhanced Oil Recovery (MEOR) process is getting much attention from researchers. A diversity of halophilic bacteria that produce biosurfactants can be found in areas with intense oil exposure, such as the waters of Bima Bay, which is closed and are one of the main sea transportation routes in eastern Indonesia. This research aims to isolate potential local halophilic bacteria in producing biosurfactants to degrade hydrocarbons. The research methodology included bacterial isolation, gram staining, hemolysis test, total petroleum hydrocarbon (TPH) analysis, emulsification, and phylogenetic analysis of the 16S rRNA marker gene. STP-GRIV-024 was successfully isolated using Kish, Halophilic, Soil extract, and Oatmeal agar media, with the highest enumeration results found on Kish media supplemented with 3% (w/v) NaCl. Microscopic morphological characterization using Gram staining showed results as a Gram-positive group with round colony shapes, smooth circular edges, sloping and white. This isolate grew in the 7-15% (w/v) NaCl range and was classified as moderately halophilic. TPH analysis showed that concentration and incubation time influenced hydrocarbon degradation activity. On day 10, the concentrations of T1 (1%), T2 (3%), T3 (5%), and T4 (7%) showed a decrease in TPH of 1.96%, 0.51%, 0.25 %, and 0.15% respectively. 16S rRNA sequencing identified the isolate as closely related to Staphylococcus haemolyticus strain MTCC3383T, with a DNA sequence similarity of 99.9%. These findings provide an important foundation for further development in applying halophilic bacteria in MEOR practices to increase the efficiency of sustainable and environmentally friendly oil production